Regulation of Bacillus subtilis macrofiber twist development by D-alanine. - Surana, U (1988)
Twist states of Bacillus subtilis macrofibers were found to vary as a function of the concentration of D-alanine in the medium during growth. L-Alanine in the same concentration range had no effect. Increasing concentrations of D-alanine resulted in structures progressively more right-handed (or less left-handed). All strains examined in this study, including mutants fixed in the left-hand domain as a function of temperature, responded to D-alanine in the same way. All twist states from tight left- to tight right-handedness could be achieved solely by varying the D-alanine concentration. The D-alanine-requiring macrofiber strain 2C8, which carries a genetic defect (dal-1) in the alanine racemase, behaved in a similar fashion. The combined effects of D-alanine and ammonium sulfate (a factor known to influence macrofiber twist development in the leftward direction) were examined by using both strains able to undergo temperature-induced helix hand inversion and others incapable of doing so. In all cases, the effects of D-alanine predominated. A synergism was found in which increasing the concentration of ammonium sulfate in the presence of D-alanine enhanced the right-factor activity of the latter. A D-alanine pulse protocol provided evidence that structures undergo a transient inversion indicative of "memory." Chloramphenicol treatment inhibited the establishment of memory in the D-alanine-induced right to left inversion, supporting the existence of a "left twist protein(s)" that is required for the attainment of left-handed twist states. Chemical analysis of cell walls obtained from right- and left-handed macrofibers produced in the presence and absence of D-alanine, respectively, failed to reveal twist state-specific differences in the overall composition of either peptidoglycan or wall teichoic acids.